2021
DOI: 10.1088/1755-1315/757/1/012084
|View full text |Cite
|
Sign up to set email alerts
|

West Sumatran Stingless Bees (Hymenoptera: Apidae: Meliponini): What can be told from its Local Distribution

Abstract: Research on stingless bee at several Meliponiculture (stingless beekeeping) sites in West Sumatra, including at Universitas Andalas Campus Complex, had been conducted from April to December 2019 by using direct survey and direct collection methods on stingless bee worker at their colony entrances. A total of 18 stingless bee species that belong to five genera were collected. Tetragonula was the genus with the highest in species number (8), followed by Homotrigona (5) and Lepidoptrigona (3). Meanwhile, Heterotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 8 publications
0
14
1
6
Order By: Relevance
“…This finding was quite different to the previous study from Bogor, West Java, which observed the peak of nest cleaning activity peaked between midday to 1 pm [8]. Stingless bee workers that perform nest cleaning can be recognized through waste material that held at its lower jaw, flight to a short distance (1-2 meters from the nest) before dumped the waste and returned to the nest [2].…”
Section: Figure 2 the Count On T Laeviceps Workers Entering Nest Per ...contrasting
confidence: 98%
See 1 more Smart Citation
“…This finding was quite different to the previous study from Bogor, West Java, which observed the peak of nest cleaning activity peaked between midday to 1 pm [8]. Stingless bee workers that perform nest cleaning can be recognized through waste material that held at its lower jaw, flight to a short distance (1-2 meters from the nest) before dumped the waste and returned to the nest [2].…”
Section: Figure 2 the Count On T Laeviceps Workers Entering Nest Per ...contrasting
confidence: 98%
“…In West Sumatra of Indonesia, the stingless beekeeping has been developed in many parts of this province. The beekeepers usually intensify flowering vegetation around their farm in order to increase the production of honey and propolis [2]. Naturally, stingless bees build their nests where the surrounding resources are supportive in providing food and nesting materials.…”
Section: Introductionmentioning
confidence: 99%
“…This study identified 10 stingless bee species from within UACC; five stingless bee species were thought to be unique as they, as far as the database could tell, were not reported from any locality outside of UACC (Table 1). These five stingless bee species not recorded to be species that reared by 16 stingless beekeeping farms in West Sumatra that were surveyed in 2019 [8]. These unique species were Homotrigona (Tetrigona) apicalis (Smith, 1857) (Figure 2a Each stingless bee species has uniqueness in morphological, behavioral and other aspects.…”
Section: Resultsmentioning
confidence: 99%
“…This field station was in neighborhood with BERF. Altogether, these four species showed potential to be domesticated, as they were frequently observed inhibiting beekeeping farms in West Sumatra [8]. A total of 66 flowering plant species were recorded as potential food sources for stingless bees; they belong to 32 families.…”
Section: Resultsmentioning
confidence: 99%
“…Woody plants, such as trees or pines, provide nesting place through natural holes formed in it or through the help of termites or other cellulose-digesting organisms. In West Sumatra, stingless bee L. terminata was recorded from Pariaman Regency [3,4]. Among other member of genus Lepidotrigona, the stingless bee L. terminata is bred by the meliponiculture practitioner in this area, where their colonies usually placed under the tree canopy or even using the shade created by the crop plants in the plantation area [5].…”
Section: Introductionmentioning
confidence: 99%